2015
DOI: 10.1890/es15-00346.1
|View full text |Cite
|
Sign up to set email alerts
|

The role of scale in designing protected area systems to conserve poorly known species

Abstract: Possingham. 2015. The role of scale in designing protected area systems to conserve poorly known species. Ecosphere 6(11):237. http://dx.doi.org/10.1890/ES15-00346.1Abstract. Systematic conservation planning has a substantial theoretical underpinning that allows optimization of tradeoffs between biodiversity conservation and other socioeconomic goals. However, this theory assumes perfect spatial information about the locations of biodiversity features (e.g., species distributions). In practice, planners repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 65 publications
2
4
0
Order By: Relevance
“…Our multivariate model and sensitivity analyses support this point, revealing that rapid area accumulation improves changes in PE when implemented through multiple, smaller PAs rather than fewer, larger PAs. Previous studies have found similar results, showing that large selection units (in our case, PAs) drive the overrepresentation of features (Pressey & Logan 1998) or allow entire features to fall into unprotected gaps (Kendall et al 2015). With large PA expansion predicted to increase in coming years in an effort to meet percent coverage targets (Blomley et al 2013), and others promoting the need for "mega reserves" (Laurance 2005), it will be important to consider the role of scale in achieving conservation outcomes.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Our multivariate model and sensitivity analyses support this point, revealing that rapid area accumulation improves changes in PE when implemented through multiple, smaller PAs rather than fewer, larger PAs. Previous studies have found similar results, showing that large selection units (in our case, PAs) drive the overrepresentation of features (Pressey & Logan 1998) or allow entire features to fall into unprotected gaps (Kendall et al 2015). With large PA expansion predicted to increase in coming years in an effort to meet percent coverage targets (Blomley et al 2013), and others promoting the need for "mega reserves" (Laurance 2005), it will be important to consider the role of scale in achieving conservation outcomes.…”
Section: Discussionsupporting
confidence: 59%
“…Previous studies have found similar results, showing that large selection units (in our case, PAs) drive the overrepresentation of features (Pressey & Logan ) or allow entire features to fall into unprotected gaps (Kendall et al . ). With large PA expansion predicted to increase in coming years in an effort to meet percent coverage targets (Blomley et al .…”
Section: Discussionmentioning
confidence: 97%
“…The positive relationship between total area protected and total PE further supports this point, as well as our model, which revealed that despite the overall increasing trends in PE, the annual Our multivariate model and sensitivity analyses support this point, revealing that rapid area accumulation improves changes in PE when implemented through multiple, smaller PAs rather than fewer, larger PAs. Previous studies have found similar results, showing that large selection units (in our case, PAs) drive the overrepresentation of features (Pressey & Logan 1998) or allows entire features to fall into unprotected gaps (Kendall et al 2015).…”
Section: Drivers Of Change In Pe: Inevitable or Deliberate?supporting
confidence: 79%
“…r packages) to easily assess adequacy of sample size, which is concerning, particularly if management strategies (e.g. boundaries of marine protected areas) are then based on insufficient sampling (Hebblewhite & Haydon, 2010; Kendall et al., 2015). A common approach to address this issue applies a pre‐defined volume contour of a UD for each tracked animal (e.g.…”
Section: Introductionmentioning
confidence: 99%